Management Control System and Organizational Performance of Cooperatives in Nepal - Singh, Prem Bahadur (Journal of Research in Education, 2025)
The focus of this paper is on the impact of Management Control Systems (MCS) on cooperatives. MCS are constructed systems through which managers can design the use of operating activities and resources so that they can be aligned with implementing organizational strategies, and they require that people be responsible for using these resources. Democracy and Ownership Cooperatives, which seek to reconcile their democratic governance and ownership dimensions with economic sustainability, must therefore have effective means of assessing both sound business performance and member trust. A questionnaire based on the ‘control’ feature of MCS was used for measuring the feature and tested along 100 cooperatives managers using a structured tool which is also based on a questionnaire that applied 5-point Likert scale as an instrument in expressing their degree of agreement, with descriptive and analytical methods in dealing with the control features (internal audit, budgeting, flexible controls and reporting systems) of MCS. In conclusion, this study emphasizes the need for a well-designed and contextually appropriate Management Control System (MCS) in cooperative enterprises to address both economic and social goals. It is positively correlated with the level of enterprise operations and competition in that (1) the internal audit demand and budget design system should be easy to operate and flexible to promote formation. These actions do more than enforce financial discipline; they encourage flexibility and innovation in management.